Perforation Peritonitis: Clinical Insights from a Three-Year Experience - Singh, Rohit Kumar; Singh, Sweta; Khanna, Soumya; Tiwary, S. K.; Puneet; Khanna, Ajay K (British Journal of Healthcare and Medical Research, 2023)
Background: Peritonitis caused by gastrointestinal perforation is a frequent surgical emergency globally. Early detection and treatment are vital in reducing complications and death. Surgical intervention and good perioperative care improve outcomes. A clinical trial assessed the outcome of perforation peritonitis at a tertiary healthcare institute to identify factors contributing to morbidity and mortality. Materials and Methods: The study conducted at IMS, BHU, was a Prospective Observational Study for 3 years. Patients of all ages presenting with acute abdominal pain and gas under the diaphragm were enrolled. After examination through different methods, after resuscitation, Laparotomy was performed in all patients, followed by thorough peritoneal lavage. The site, size, type, and number of perforations were documented, and biopsy was taken from the edge of the perforation when necessary. Results: The study showed that duodenal ulcer perforation was the leading cause of gastrointestinal perforation, followed by appendicitis, typhoid perforation, and malignancy. Primary closure was the most common surgical procedure, followed by appendectomy, gut resection, and exteriorization. Mortality rate was , and observed morbidity included wound infection, fever, respiratory complications, residual abscess, electrolyte imbalances, burst abdomen, sepsis, cardiac complications, and anastomotic disruption. Conclusion: Gastrointestinal perforation is a common complication of acid peptic disease and typhoid. To control acid peptic disease, NSAIDs and triple therapy for H. pylori eradication can be used. Early and primary treatment for typhoid should be prioritized on a larger scale, and common practitioners should be educated to increase awareness about the disease.